EVALUATION OF Zingiber officinae Rosc. EXTRACTS AGAINSTPATHOGENIC BACTERIA - Albayati, Maysson; Jawad, Abdul-latif; Khudir, Marwa (Iraqi Journal of Science, 2024)
This research has been performed to assess the antibacterial efficiencies of thecrude extracts of dried rhizome powder of Zingiber officinale plant. These extractswere obtained by using different organic solvents and water.Results revealed that diethylether and ethanolic extracts have shown an inhibitoryaction upon both Gram positive and Gram negative bacteria in concentrationsbetween (10–100) mg/ml.Cold water extracts showed higher inhibitory activity than that of the hot waterextract. These results obtained by using the well diffusion method. In addition allthese results were comparised with some classical antibiotics such as Erythromycin,Amoxycillin, Ampicillin and others. The extracts showed higher inhibitory activitythan these antibiotics were used except the extract which was obtained by hot water.